Penglibatan kaum wanita dalam aktiviti keusahawanan di Negeri Johor : kajian terhadap faktor-faktor kritikal kejayaan dan kegagalan pengendalian perniagaan - Abu Bakar, Thuaibah @ Suaibah (Faculty of Management and Human Resources Development, 2005)
The purpose of this research is to identify the factors that influence women in their involvement, achievement and failure in business. Besides that, this research also tries to identify problems that always facing by women entrepreneurs while starting and handling their business. Questionnaire has been used as a method of data collection in this research and has been distributed to 215 women entrepreneurs that involve in entrepreneurship in Johor. Then the data have been analyzed by using Statistical Package For Social Science (SPSS) 10.0 to get frequency, percentage and mean. Generally, the result of this research shows three main factors that influence women to become entrepreneur were because of their attention to business, ambition and independence. This research also found that attitude is an element that most influence women’s achievement while skills are an element that most influence women’s failure in handling business.